The uniqueness of family business - Kong, Lai Kuan; Ahmad, Siti Hasziani; Ju, Soon Yew (Universiti Teknologi MARA, Terengganu, 2022)
Family business has long been existed. The very oldest family business in the world is Japanese temple-builder Kongo Gumi, which founded in 578. While in Malaysia, family businesses have dominated industries of all types and sizes. Among the well-known family businesses in Malaysia are for instance IOI Group, Genting Group, YTL, to name a few. Despite its long existence, scholars such as Astrachan, Klein, & Smyrnios, (2002) found that there is no universally accepted definition(s) assigned to family business. As in Malaysia context, till date, there is neither established statistical information on family business nor any official agency registered them.